Price and Quantity Contracts in a Mixed Duopoly with a Socially Concerned Firm. (28th November 2014) - Kopel, Michael
Abstract : I study the endogenous choice of a price or quantity contract in a mixed duopoly with a socially concerned firm, which maximizes a combination of profit and consumer welfare. Equilibria with price and quantity contracts might co‐exist; welfare under price competition might be lower than under quantity competition; the firms' profit ranking might be different from that of a private duopoly or mixed duopoly with a public firm. Hence, if a firm follows a social strategy, the optimal market strategy crucially depends on the levels of social concern and competition in the market. The presence of socially concerned firms may change the mode of competition. Copyright © 2014 John Wiley & Sons, Ltd.